2012
DOI: 10.1371/journal.pone.0050414
|View full text |Cite
|
Sign up to set email alerts
|

Suppression Subtractive Hybridization Reveals Transcript Profiling of Chlorella under Heterotrophy to Photoautotrophy Transition

Abstract: BackgroundMicroalgae have been extensively investigated and exploited because of their competitive nutritive bioproducts and biofuel production ability. Chlorella are green algae that can grow well heterotrophically and photoautotrophically. Previous studies proved that shifting from heterotrophy to photoautotrophy in light-induced environments causes photooxidative damage as well as distinct physiologic features that lead to dynamic changes in Chlorella intracellular components, which have great potential in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In order to target the genes related to TAG accumulation and learn more about the transcriptional changes in response to nutrient limitation in microalgae, we made an initial effort to search differentially expressed genes using the suppression subtractive hybridization approach under trophic transition: the results indicated that the transition from heterotrophy to photo-induction culture can stimulate lipid accumulation in Chlorella coupled with a series differentially expressed genes in the lipid metabolic pathway [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to target the genes related to TAG accumulation and learn more about the transcriptional changes in response to nutrient limitation in microalgae, we made an initial effort to search differentially expressed genes using the suppression subtractive hybridization approach under trophic transition: the results indicated that the transition from heterotrophy to photo-induction culture can stimulate lipid accumulation in Chlorella coupled with a series differentially expressed genes in the lipid metabolic pathway [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…To model the temporal process featuring the switch of the intracellular metabolite profile from one dominated by starch to one dominated by proteins and lipids, we changed the C. pyrenoidosa cultivation mode from heterotrophy to photoautotrophy at 72 h (Fan et al, 2012a(Fan et al, , 2012bHan et al, 2012), followed by a 48-h light illumination. At each of the six time points during this SHDP process, three biological replicates of separate culture experiments were each sampled for transcriptome analysis via deep mRNA sequencing and metabolite analysis (Fig.…”
Section: Transcriptome Dynamics During the Switch Processmentioning
confidence: 99%
“…Remarkably, when cells are shifted from heterotrophic to photoautotrophic conditions, a short duration (1 to 2 d depending on the weather) of illumination induces a prominent change in the intracellular profile, with marked decreases in starch yet 70% to 120% increases in lipids and proteins (Fan et al, 2012a(Fan et al, , 2012bHan et al, 2012;Li et al, 2014b), resulting in both high target product contents (lipids and proteins) and high biomass productivity ( Fig. 1; Supplemental Fig.…”
mentioning
confidence: 99%
“…Instead, other Chlorella species have been cultivated under mixo– and heterotrophic conditions for the production of lutein and astaxanthin (antioxidants) and have served as the basis for mathematical models of sugar-based growth [39] – [44] . Recent metabolic flux analyses and transcriptomic studies performed under different trophic conditions also provide compelling information about shifts in Chlorella lipid metabolism [21] , [45] [47] .…”
Section: Introductionmentioning
confidence: 99%